Kecerdasan emosi dan komitmen pekerjaan dalam kalangan pensyarah universiti di Indonesia - Iskandar,; Rohaty Mohd. Majzub,; Zuria Mahmud, (penerbit ukm, 2009)
The aim of this study is to identify the profiles of emotional quotient and work commitment among 265 university lecturers in Indonesia. Instruments used to gather data for this research are the Inventori Kepintaran Emosi Malaysia (IKEM), or Malaysian Emotional Quotient Inventory (MEQI), and an instrumen measuring the work commitment of university lecturers. Descriptive statistics test showed from the Emotional Quotient Inventory, the lecturers scored highest in the spiritual and maturity domains, medium in motivation, self regulation, and empathy, and lowest in self awareness and social skills. Research also shows significant differences in emotional quotient among the lecturers based on age group and working experience, and significant difference in work commitment based on age group, education level, and work experience. Results show a significant relationship between emotional quotient and work commitment. Regression shows that social skill dimension in the emotional quotient contribute significantly towards work commitment. Information from this study is hoped to be useful for policy makers of higher education in Indonesia in their efforts to alleviate the work quality of university lecturers.